DEVELOPMENT OF INTERNATIONAL FINANCIAL FISCAL STANDARDS IN ACCORDANCE WITH THE ROLE OF IASB - Shaheen, Ali Murtadha (Journal of Economic, Administrative and Legal Sciences, 2019)
The objective of the research is to demonstrate the role of International Accounting Standards Board in the development of International Financial Reporting Standards to support the efficiency of international capital markets from 1973 to 2011, and then to measure the impact of the application of IFRS in accordance with the role of the International Accounting Standards Board. There have been differences in the market, volumes of the first and second markets and in the share price index, refer to market value, trading volumes yet trading volumes appropriate according to the software over International Financial Reporting Standards between the training on monetary statements of agreement stock companies.